Darkness as a metaphor in the historiography of the Enlightenment - Tunturi, Janne (Approaching Religion, 2011)
This paper concentrates on darkness as a metaphor in eighteenth century historical writing. In contrast to the celebration of light as a symbol of knowledge and progress, the interpretations of the meaning of darkness varied. For many historians, it symbolised backwardness, or decline, which culminated in medieval society. Yet, the relationship between eighteenth century historiography and the Middle Ages was not as explicit as the usual suspects such as Voltaire and Edward Gibbon suggest. First of all, the understanding of the culture or texts of the Dark Ages signalled the skilfulness of the interpreter. Secondly, some supposed features of the medieval culture, such the free use of the imagination, gradually became more appreciated.